Challenges to the treatment and new perspectives for the eradication of helicobacter pylori - Yazbek, Priscila Baptistella [UNESP]; Trindade, Ariane Biolcati [UNESP]; Chin, Chung Man [UNESP]; Dos Santos, Jean Leandro [UNESP] (Digestive Diseases And Sciences, 2015)
Helicobacter pylori (H. pylori) is one of the leading causes of gastric diseases such as chronic gastritis, peptic ulcer, and gastric adenocarcinoma. The current treatment of H. pylori infection with antibiotics and proton pump inhibitors has several limitations, including poor adherence and intrinsic patient-related factors, drug resistance, and the absence of adequate treatments. This review summarizes the current therapeutic approaches to eradicating H. pylori, the difficulties associated with its treatment, and several new perspectives aimed at improving existing treatment strategies.
Keywords: Gastric diseases; H. pylori eradication; H. pylori resistance; Helicobacter pylori; Treatment